Tin in Souteastern Europe? - Durman, Aleksandar (Array, 1997)
Apart from Cornwall, the only indisputable source of tin in the prehistoric Europe, some new potential sources in Souteastern Europe (on the mountains Bukulja and Cer in western Serbia), should be considered. The fortunate coincidence, that the deposits of copper and tin ore were found close to each other, very likely played the crucial role in the production of full-flegged bronze towards the end of the Vučedol Culture (phase C).